Exploring Omani EFL students’ written linguistic accuracy development in disciplinary contexts - Naghdipour, Bakhtiar; Kadhim, Kais Amir (Penerbit Universiti Kebangsaan Malaysia, 2021)
It is generally assumed that undergraduate students’ L2 written linguistic accuracy develops naturally in academic contexts as they engage in disciplinary content. To provide evidence of linguistic accuracy development in EFL writing, this study examines university students’ ability to identify and correct linguistic errors (spelling, grammar and punctuation) in their writing and the mediational means or resources they consult to deal with such errors in disciplinary contexts. A mixed-method approach was employed to collect quantitative and qualitative data from undergraduate students (N = 60) who took a first-year essay writing course at a major university in Oman. In addition, Fourth-year, third-year, and second-year students majoring in social sciences proofread their essays written for the course final exam in the first semester of their studies. All participants were also interviewed to obtain insights into the likely resources and strategies they used to improve the linguistic accuracy of their writing. The results revealed that the length of the study was not a key factor affecting students’ written linguistic accuracy development, as fourth-year students significantly outperformed their counterparts only in identifying and fixing the surface-level spelling and punctuation errors. Furthermore, the students’ use of learning strategies and resources varied depending on individual factors such as future academic goals and career prospects. The paper concludes with a discussion of pedagogical implications and future research directions in EFL contexts.